Ancestral reconstruction of the MotA stator subunit reveals that conserved residues far from the pore are required to drive flagellar motility. (3rd April 2023) - Islam, Md Imtiazul; Ridone, Pietro; Lin, Angela; Michie, Katharine A; Matzke, Nicholas J; Hochberg, Georg; Baker, Matthew A B
Abstract: The bacterial flagellar motor (BFM) is a rotary nanomachine powered by the translocation of ions across the inner membrane through the stator complex. The stator complex consists of two membrane proteins: MotA and MotB (in H + -powered motors), or PomA and PomB (in Na + -powered motors). In this study, we used ancestral sequence reconstruction (ASR) to probe which residues of MotA correlate with function and may have been conserved to preserve motor function. We reconstructed 10 ancestral sequences of MotA and found four of them were motile in combination with contemporary Escherichia coli MotB and in combination with our previously published functional ancestral MotBs. Sequence comparison between wild-type (WT) E. coli MotA and MotA-ASRs revealed 30 critical residues across multiple domains of MotA that were conserved among all motile stator units. These conserved residues included pore-facing, cytoplasm-facing, and MotA–MotA intermolecular facing sites. Overall, this work demonstrates the role of ASR in assessing conserved variable residues in a subunit of a molecular complex.